EFL PRE-SERVICE TEACHERS’ PROFESSIONAL IDENTITY CONSTRUCTION THROUGH REFLECTIVE MENTORING DURING TEACHING PRACTICUM - Ardi, Priyatno; Widiati, Utami; Suryati, Nunung; Wulyani, Anik Nunuk (LLT Journal: A Journal on Language and Language Teaching, 2025)
Mentoring in language teacher education has been widely acknowledged to foster pre-service teachers’ reflective practice. While previous studies have focused on pre-service teachers’ practical teaching skills, their cultivation of inner professional selves remains under-researched. For this reason, this study aims to examine how reflective mentoring catalyzes EFL pre-service teachers’ professional identity construction during teaching practicum. A case study design was employed in this study. Two mentors (one male and one female) and four EFL pre-service teachers (two males and two females), who were purposefully selected, participated in this study. Data were collected through video-recording ten mentoring sessions and interviewing both the mentors and pre-service teachers. Thematic analysis was then employed to analyze the data. The findings revealed that the reflective mentoring catalyzed the pre-service teachers’ professional identity construction during teaching practicum by creating a systematic and supportive space for reflecting on temporal, theoretical, and practical experiences. The space arose from five factors in the mentoring, including systematic processes of reflection, non-judgmental and supportive mentors, interpersonal bonds and interconnectedness, past and present connections, and theory-practice continuums. Reflection particularly contributed to the identity construction since it allowed the pre-service teachers to examine their professional experiences and derive meaning for their professional identities. Based on the findings, this study suggests that mentoring during teaching practicum should encompass both the practical aspects of teaching and the inner professional selves of EFL pre-service teachers.